1972
DOI: 10.1113/expphysiol.1972.sp002160
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Glucose in the Oxidative Metabolism of the Pregnant Uterus and Its Contents in Conscious Sheep With Some Preliminary Observations on the Oxidation of Fructose and Glucose by Fetal Sheep

Abstract: The day after implantation of catheters under general anaesthesia, u-[14C] glucose was infused intravenously into four conscious ewes about 130 days pregnant, and into two fetuses about 130 days old. u-[14C] fructose was infused into three other similar fetuses.It could be calculated that the pregnant uterus with its contents derived about 40% of its CO2 from blood glucose and oxidized directly about 45% of the glucose utilized. The total uptake of glucose by the uterus and contents accounted for about 70% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1974
1974
2005
2005

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Alexander, Britton & Nixon (1970) demonstrated that in an artificially perfused fetal sheep preparation the rate of oxidation of fructose was much less than that of glucose. By contrast, Setchell, Bassett, Hinks & Graham (1972) inferred from a limited number of observations in intact pregnant ewes that there is little difference in the contribution of fetal glucose and fructose carbon to fetal CO2 turnover.…”
Section: Introductionmentioning
confidence: 94%
“…Alexander, Britton & Nixon (1970) demonstrated that in an artificially perfused fetal sheep preparation the rate of oxidation of fructose was much less than that of glucose. By contrast, Setchell, Bassett, Hinks & Graham (1972) inferred from a limited number of observations in intact pregnant ewes that there is little difference in the contribution of fetal glucose and fructose carbon to fetal CO2 turnover.…”
Section: Introductionmentioning
confidence: 94%
“…These techniques have proved invaluable for studying metabolism in specific tissues, as exemplified by the studies of the mammary gland by Linzell (1974), and similar work on the liver and gut (Bergman and Wolff 1971), a defined muscle mass in the leg (Domanski et al 1974), the pregnant uterus (Setchell et al 1972) and the fetus and placenta (Battaglia and Meschia 1978).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic conse quences for the human fetus of such a treatment are not fully known, having been studied mainly by single-point determinations of biochemical param eters in fetal blood [Paterson et al, 1967a;A n d erson et al, 1970], The opin ion has recently been expressed that glucose load to parturients may adverse ly increase the acidosis in the oxygen-deprived fetus owing to a rise of plasma lactate [Shelley, 1973]. Furthermore, the role of glucose as the predominant source of energy for fetal metabolism [Sabata et al, 1968;A lexander et al, 1969] has recently been challenged [Setchell et al, 1972;Battaglia and M eschia, 1973] but the alternatives of metabolic fuel are not yet completely defined. The metabolic effects of glucose administration prenatally are thus of great physiological and clinical importance.…”
Section: Introductionmentioning
confidence: 99%